Prostatic artery embolisation versus medical treatment in patients with benign prostatic hyperplasia (PARTEM): a randomised, multicentre, open-label, phase 3, superiority trialResearch in context - Marc Sapoval; Nicolas Thiounn; Aurélien Descazeaud; Carole Déan; Alain Ruffion; Gaële Pagnoux; Ricardo Codas Duarte; Grégoire Robert; Francois Petitpierre; Gilles Karsenty; Vincent Vidal; Thibaut Murez; et al. (Elsevier, 2023)
Summary: Background: Prostatic artery embolisation (PAE) is a minimally invasive treatment of symptomatic benign prostatic hyperplasia (BPH). Our aim was to compare patient's symptoms improvement after PAE and medical treatment. Methods: A randomised, open-label, superiority trial was set in 10 French hospitals. Patients with bothersome lower urinary tract symptoms (LUTS) defined by International Prostatic Symptom Score (IPSS) > 11 and quality of life (QoL) > 3, and BPH ≥50 ml resistant to alpha-blocker monotherapy were randomly assigned (1:1) to PAE or Combined Therapy ([CT], oral dutasteride 0.5 mg/tamsulosin hydrochloride 0.4 mg per day). Randomisation was stratified by centre, IPSS and prostate volume with a minimisation procedure. The primary outcome was the 9-month IPSS change. Primary and safety analysis were done according to the intention-to-treat (ITT) principle among patients with an evaluable primary outcome. ClinicalTrials.gov Identifier: NCT02869971. Findings: Ninety patients were randomised from September 2016 to February 2020, and 44 and 43 patients assessed for primary endpoint in PAE and CT groups, respectively. The 9-month change of IPSS was −10.0 (95% confidence interval [CI]: −11.8 to −8.3) and −5.7 (95% CI: −7.5 to −3.8) in the PAE and CT groups, respectively. This reduction was significantly greater in the PAE group than in the CT group (−4.4 [95% CI: −6.9 to −1.9], p = 0.0008). The IIEF-15 score change was 8.2 (95% CI: 2.9-13.5) and −2.8 (95% CI: −8.4 to 2.8) in the PAE and CT groups, respectively. No treatment-related AE or hospitalisation was noticed. After 9 months, 5 and 18 patients had invasive prostate re-treatment in the PAE and CT group, respectively. Interpretation: In patients with BPH ≥50 ml and bothersome LUTS resistant to alpha-blocker monotherapy, PAE provides more urinary and sexual symptoms benefit than CT up to 24 months. Funding: French Ministry of Health and a complementary grant from Merit Medical.